1998
DOI: 10.1094/pdis.1998.82.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Application of Organic and Inorganic Salts for Suppression of Silver Scurf on Potato Tubers

Abstract: Seven organic and inorganic salts were tested for suppression of silver scurf, a postharvest disease of potato tubers caused by Helminthosporium solani. Potassium sorbate, calcium propionate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonium bicarbonate were added to V8 agar at concentrations of 0.06–0.2 M. Radial growth of H. solani was significantly reduced (P < 0.05) by all salts at all concentrations. All salts except sodium bicarbonate and potassium bicarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
80
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 30 publications
5
80
0
3
Order By: Relevance
“…For each potassium salt tested, the exact concentration required to inhibit fungal growth differed somewhat between tomato pathogens. These results are consistent with other studies demonstrating that suppression of microbial strains varies in response to different organic and inorganic salts Olivier et al and Fagundes et al, [17,35] show that the percentage of fungal inhibition in amended PDA medium was dependent on concentration used, and that the most significant decrease in mycelial growth was obtained with the highest concentration of salt tested. In fact, the effectiveness of potassium salts in controlling various plant pathogens have been previously reported [18,[36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…For each potassium salt tested, the exact concentration required to inhibit fungal growth differed somewhat between tomato pathogens. These results are consistent with other studies demonstrating that suppression of microbial strains varies in response to different organic and inorganic salts Olivier et al and Fagundes et al, [17,35] show that the percentage of fungal inhibition in amended PDA medium was dependent on concentration used, and that the most significant decrease in mycelial growth was obtained with the highest concentration of salt tested. In fact, the effectiveness of potassium salts in controlling various plant pathogens have been previously reported [18,[36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 93%
“…In the same sense, Mecteau et al, [18] showed that the organic anions sorbate completely inhibit mycelial growth of F. sambucinum, the causal agent of potato dry rot, at 0.2 M, while for spore germination the ED50 was 0.56 mM. Sorbate has also shown toxicity on mycelium of Helminthosporium solani, an important potato pathogen and always ranked first in efficacy, since it was fungicidal at concentrations as low as 0.05 M [17]. Sorbate has also shown toxicity on mycelium of Helminthosporium solani, an important potato pathogen and always ranked first in terms of efficacy [17].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations